Learning path real-time data applications - Stryker, Ruth; Shapira, Gwen; Nathan, Paco; McFadin, Patrick (O'Reilly, 2015)
"There are a variety of useful applications for real-time data, including quick identification of general patterns and trends in data, performing sentiment analysis, crafting responses in real-time, and--perhaps one of the most important uses--when having analysis immediately will change the outcome of the situation. This Learning Path provides an in-depth tour of technologies used in processing and analyzing real-time data."--Resource description page.
Title from resource description page (viewed March 14, 2016)
Keywords: Apache Cassandra; Apache Kafka; Apache Spark; Databases; Electronic data processing; Application software -- Development; Logiciels d'application; Développement; Application software; Development